The genera Smicridea McLachlan and Chimarra Stephens in French Guiana (Trichoptera: Hydropsychidae, Philopotamidae) - Gibon, François-Marie; Sganga, Julieta V. (Zootaxa, 2019)
A brief collecting exploration to small streams in the coastal zone of French Guiana resulted in the capture of eight species belonging to the genus Smicridea McLachlan 1871 and two belonging to the genus Chimarra Stephens 1829. Given the scarcity of knowledge about the trichopteran fauna of this territory, the results of the study of this material are provided. A new species of the genus Smicridea is described: Smicridea (Rhyacophylax) sanctorum sp. n. Six species of Smicridea are new for French Guiana: Smicridea (R.) abrupta Flint 1974, Smicridea (R.) caligata Flint 1974, Smicridea (R.) columbiana Ulmer 1905, Smicridea (R.) pseudolobata Flint 1978, Smicridea (S.) obliqua Flint 1974, and Smicridea (S.) truncata Flint 1974. These results bring the number of French Guianan Smicridea species to 16. The two Chimarra species represent the first species records of the genus in French Guiana.